2014
DOI: 10.1289/ehp.1306627
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution Exposures During Adulthood and Risk of Endometriosis in the Nurses’ Health Study II

Abstract: Background: Particulate matter and proximity to large roadways may promote disease mechanisms, including systemic inflammation, hormonal alteration, and vascular proliferation, that may contribute to the development and severity of endometriosis.Objective: Our goal was to determine the association of air pollution exposures during adulthood, including distance to road, particulate matter < 2.5 μm, between 2.5 and 10 μm, and < 10 μm, (PM2.5, PM10–2.5, PM10), and timing of exposure with risk of endometriosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…While the effect sizes found in this study are small and strictly suggestive, they are consistent with the literature regarding air pollution and reproductive tract diseases in this cohort (Mahalingaiah et al, 2014a(Mahalingaiah et al, , b, 2016. Menstrual irregularity alone has been previously used as a proxy for PCOS in analyses within the NHSII, and this definition has provided insights into the long-term health outcomes associated with menstrual irregularity, including cardiovascular disease and diabetes (Solomon et al, 2001(Solomon et al, , 2002.…”
Section: Discussionsupporting
confidence: 92%
“…While the effect sizes found in this study are small and strictly suggestive, they are consistent with the literature regarding air pollution and reproductive tract diseases in this cohort (Mahalingaiah et al, 2014a(Mahalingaiah et al, , b, 2016. Menstrual irregularity alone has been previously used as a proxy for PCOS in analyses within the NHSII, and this definition has provided insights into the long-term health outcomes associated with menstrual irregularity, including cardiovascular disease and diabetes (Solomon et al, 2001(Solomon et al, , 2002.…”
Section: Discussionsupporting
confidence: 92%
“…Since model predictions can be made at a subject’s residence or other relevant point location, rather than interpolated from a pre-defined grid, our models offer high spatial resolution which may reduce exposure error when estimating chronic exposures in epidemiologic studies, as has been shown in previous analyses [ 11 , 25 , 26 ]. The models have been used to provide PM 2.5 , PM 10 , and PM 2.5–10 monthly exposure estimates at subject residences in recent epidemiologic analyses [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although cases have not been validated by medical records, the validity of these registered nurses' reports for many other health outcomes is generally high (.90%) (19)(20)(21)(22)(23) and provides reassurance about the accuracy of these reports. Moreover, in the Black Women's Health Study, investigators observed a very high agreement (96%) between self-report of sarcoidosis diagnosis and physician's report (4); an even higher BRIEF COMMUNICATION agreement might be expected in NHSII, which is a study of registered nurses.…”
Section: Discussionmentioning
confidence: 99%
“…U.S. region at baseline, with updating every 2 years thereafter, was categorized into four groups (West, Midwest, South, Northeast). Although the NHSII participants initially resided in 14 states, as of the mid-1990s they resided in all 50 states and the District of Columbia (21).…”
Section: Methodsmentioning
confidence: 99%